Advancements in Development of Chemical-Looping Combustion: A Review - He Fang; Li Haibin; Zhao Zengli (International Journal of Chemical Engineering)
Chemical-looping combustion (CLC) is a novel combustion technology with inherent separation of greenhouse CO2. Extensive research has been performed on CLC in the last decade with respect to oxygen carrier development, reaction kinetics, reactor design, system efficiencies, and prototype testing. Transition metal oxides, such as Ni, Fe, Cu, and Mn oxides, were reported as reactive species in the oxygen carrier particles. Ni-based oxygen carriers exhibited the best reactivity and stability during multiredox cycles. The performance of the oxygen carriers can be improved by changing preparation method or by making mixedoxides. The CLC has been demonstrated successfully in continuously operated prototype reactors based on interconnected fluidized-bed system in the size range of 0.3–50 kW. High fuel conversion rates and almost 100%  CO2 capture efficiencies were obtained. The CLC system with two interconnected fluidized-bed reactors was considered the most suitable reactor design. Development of oxygen carriers with excellent reactivity and stability is still one of the challenges for CLC in the near future. Experiences of building and operating the large-scale CLC systems are needed before this technology is used commercially. Chemical-looping reforming (CLR) and chemical-looping hydrogen (CLH) are novel chemical-looping techniques to produce synthesis gas and hydrogen deserving more attention and research.